Pemisahan Delapan Vitamin Larut Air secara Kromatografi Pasangan Ion - NOVI YANTIH (Fakultas Farmasi Universitas Pancasila, 2009)
Ion-pair chromatography is applicable for separating mixtures of acids and bases, either in ionic or nonionic form, such as mixture of ascorbic acid, thiamine hydrochloride, riboilavin, nicotinamide, pyridoxine hydrochloride, folic acid, and cyanocobalamine, and menadion sodium bisulphite. Separation using ion-pair chromatography is highly influenced by the type and concentration of the counter ion and the selected pH of mobile phase. Eight Water soluble vitamins Were separated in a single analysis Withtotal analysis time never exceeded 12 minutes by using a reversed-phase column (CS) with a mixture of methanol and solution of 5 mM sodium hexanesulphonate at pH 3.50 (49: 151) as mobile phase, at a flow rate of l ml per minute, and ultraviolet detector at 275 nm. Satisfactory separation was shown by the resolution values of more than 1.5, which were between 3.8-10.6.